THE EFFECT OF HISTORICAL AWARENESS AND ATTITUDES OF NATIONALISM ON THINKING CRITICAL HISTORY IN CLASS XI SMAN 1 GAMPING - Melani, Devi (Satmata: Journal of Historical Education Studies, 2023)
This study aims to: (1) Find out how high the level of quality of critical thinking, historical awareness and attitudes of nationalism in class XI SMAN 1 Gamping. (2) Knowing the effect of historical awareness on students' critical thinking in class XI of SMAN 1 Gamping. (3) Knowing the effect of the attitude of nationalism on the historical critical thinking of students in class XI of SMAN 1 Gamping. (4) Knowing together between the influence of historical awareness and the attitude of nationalism on critical thinking in class XI SMAN 1 Gamping. Research with a quantitative approach to survey methods and research instruments using a questionnaire. The population used was 145 students of class XI at SMAN 1 Gamping, while the sample used was 105 students with an error rate of 5%. The results showed that: (1) The level of critical thinking quality was 81.10%, historical awareness was 86.60%, and the attitude of nationalism was 88.30%. There is a positive and significant influence on historical awareness with critical thinking of 0.550. There is a positive and significant influence between the attitude of nationalism and critical thinking of 0.579. There is a positive and significant influence jointly between historical awareness and nationalism attitudes with critical thinking of 0.624.